Opportunities and Constraints of International Banana Shipping in Local Socioeconomic Development: the Costa Rican Caribbean Case - Mora Barahona, Aarón (2024)
The purpose of this article is to consider the opportunities and limitations of the international transport of bananas in the socioeconomic development of the Costa Rican Caribbean from a historical perspective. This is bibliographical research based on the analysis of secondary sources. The province of Limón's potential to boost its economy through banana exports is exposed. Still, structural difficulties that have prevented the full development of this region have also been raised. To do this, the conditions of its foundation are compared to its current situation to identify the inherited socioeconomic factors and the unresolved problems. The main finding is that the banana production chain develops in border areas where it becomes necessary to integrate local action plans with cross-border and inter-institutional efforts to generate real opportunities that improve the living conditions of the inhabitants of the Costa Rican Caribbean.